Cutoff-independent regularization of four-fermion interactions for color superconductivity - Farias, R. L.S. [UNESP]; Dallabona, G. [UNESP]; Krein, G. [UNESP]; Battistel, O. A. (American Physical Society (APS), 2006)
We implement a cutoff-independent regularization of four-fermion interactions to calculate the color-superconducting gap parameter in quark matter. The traditional cutoff regularization has difficulties for chemical potentials μ of the order of the cutoff Λ, predicting in particular a vanishing gap at μ~Λ. The proposed cutoff-independent regularization predicts a finite gap at high densities and indicates a smooth matching with the weak coupling QCD prediction for the gap at asymptotically high densities. © 2006 The American Physical Society.